SPATIO-TEMPORAL ANALYSIS OF CHANGES IN CORAL REEF AREA USING LANDSAT 8 SATELLITE IMAGERY ON PARI ISLAND, KEPULAUAN SERIBU, DKI JAKARTA - Akmal, Faisal; Semedi, Bambang; Ulfa, Azura (Ikatan Geografi Indonesia, 2024)
Coral reefs are ecosystems that are sensitive to change. High pressure can cause damage to coral reefs. Monitoring the condition of coral reefs needs to be done to know the current condition. One way that can be used to monitor coral reefs is by utilizing remote sensing. The research was conducted to know the changes in the coral reef area and the factors that influence the changes in the coral reef area in Pari Island, Kepulauan Seribu, DKI Jakarta in the period 2013 to 2022. The research was conducted using Landsat 8 image data from 2013 to 2022. Image data processing was done with an object-based classification method. Coral cover measurements were conducted using the Line Intercept Transect (LIT) method. The results showed a change in coral reef area of 7.02 ha with the condition of live coral cover ranging from 27-43% which is included in the fair category. The results of field measurements show that the condition of water parameters falls into the unsuitable category. The increase in area that occurred was thought to be due to management activities carried out by the Pari Island community and activities carried out by LIPI in 2016, namely conducting coral reef restoration. The decrease in area is partly due to coastal reclamation activities, destructive tourist activities, and parameter conditions.